Evolution of microbial ecology: A rare multidrug-resistant (Enterobacter Cloacae) surgical wound infection after cesarean delivery: Our experience of 5946 cesarean deliveries - Bayramoglu, Zeynep; Okuyan, Erhan; Tay, Hayrettin; Yoldas, Adem (Annals of Medical Research, 2021)
None
Keywords: Evolution of microbial ecology; multidrug-resistant Enterobacter Cloacae; surgical wound infection